„DER GOLDENE SARG“ – DIE OPER DES „DEBUSSYS DER THEIßGEGEND“ IM SPIEGEL IHRES TONSYSTEMS - ILLÉS, Mária (Studia Universitatis Babes-Bolyai Musica, 2011)
„The Golden Coffin” – Opera by “Debussy from Tisza-part” in the Mirror of his Tone System. Vántus István, the determining personality of the musical life of the 20th century in Szeged would be 75 years old in 2010, and it is the 35th anniversary of his opera Golden Coffin. This opera is one of the greatest pieces of music which can be related to Szeged and which deserves this rank because of its size, quality and importance as well. Vántus made the libretto from the novel Golden Coffin, which takes places in the era of Emperor Diocletian. Móra Ferenc, who was also born in Szeged, wrote the novel. The whole piece is in the tonal system of the so called “infinite pentatonality”, which was created by Vántus in the 1960s, and then he built up his whole life-work on the basis of this special system, which originates in the Hungarian folk pentatonality, but it contains the potentials of modern sonority as well. By presenting Golden Coffin I would like to make an approach to Vántus’s mentality as a composer, analysing it from the dual points of view of theory and practice.